An Investigation of Fin and Blue Whales in the NE Pacific Ocean using Data from Cascadia Initiative Ocean Bottom Seismometers - Wilcock, William S; Mellinger, David K (2014)
The long-term goals of this project are to develop, evaluate and compare techniques to estimate fin and blue whale locations and densities from ocean bottom seismometer (OBS) data and thus enable the research community to better utilize the increasing number of OBS earthquake monitoring studies near continental margins to understand the distribution and behavior of baleen whales. Prepared in collaboration with the Cooperative Institute for Marine Resources Studies, Oregon State University, Newport.